Fryderyk Chopin in popular instrumental music - Kasperski, Jakub (Interdisciplinary Studies in Musicology, 2018)
The author considers whether Fryderyk Chopin and his oeuvre may be regarded as part of popular culture - and if so, to what extent. However, the text is mostly taken up with analysis of popular instrumental music inspired by Chopin’s works in various ways: from simple quotation, adaptation and transcription to more sophisticated instrumentation and arrangement, free improvisation or even the creation of a completely new work derived from a single motif or sample from Chopin. Consequently, the author deals with the problem of reception, but also with the issue of transculturation and the relationship between high and popular culture. The article shows and describes the variety of Chopin inspiration in a wide range of styles and genres of popular music, such as rock music, easy-listening, electronic music, dance music and disco.